ANALISIS KEMAMPUAN BERPIKIR KRITIS (CRITICAL THINKING) SISWA DALAM MENGERJAKAN SOAL HOTS PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS V SDN 42 CAKRANEGARA TAHUN PELAJARAN 2025/2026 - Jayanti, Putri; Mulabbiyah; Silka Yuanti Draditaswari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of critical thinking skills in facing 21st-century educational challenges, particularly in solving Higher Order Thinking Skills (HOTS) questions in Indonesian language subjects. The primary objective of this study is to analyze the critical thinking skills of fifth-grade students at SDN 42 Cakranegara for the 2025/2026 academic year in completing these HOTS questions. This study focuses on the process and level of students' ability to apply critical thinking indicators when dealing with high-level questions. This study used a qualitative approach with a descriptive design. Data were collected through Multiple Choice Multiple Answer (MCMA) test instruments, in-depth interviews, and documentation to obtain a comprehensive overview of students' abilities. The results showed that students' critical thinking skills were in the moderate category with varying achievements in each indicator. The analysis or problem identification indicator became the aspect with the highest achievement because students were able to connect information components quickly and confidently without having to read the text repeatedly. Conversely, the inference indicator became the aspect with the lowest achievement due to significant obstacles in concluding the implicit meaning of a text. Meanwhile, the interpretation, evaluation, and explanation indicators were in the moderate category because students tended to rush and had limited mastery of technical language vocabulary such as the term "pronominal." This study concludes that there is a positive dynamic in the form of students' independent efforts to understand questions through self-correction techniques, but teacher reinforcement through guided reading strategies and intensive HOTS question practice remains highly necessary.